PRE-FRAILTY IN OLDER ADULTS: PREVALENCE AND ASSOCIATED FACTORS. - Delmondes de Oliveira, Adriana; de Oliveira Reiners, Annelita Almeida; Souza de Azevedo, Rosemeiry Capriata; Moreira da Silva, Kátia; Candido da Silva, Ageo Mário (Texto & Contexto Enfermagem, 2022)
Objective: to analyze pre-frailty prevalence in older adults residing in the community and associated factors. Method: a cross-sectional study, carried out with 291 elderly people registered in Family Health Strategy units. Pre-frailty was measured using the Edmonton Frail Scale, and the other variables were measured using different instruments. Data were collected from June to August 2018. Data analysis was performed using the Mantel Haenszel chi-square test, Fisher's test and Poisson multivariate regression. Results: pre-frailty prevalence was 69.42% (95% CI; 63.77%-74.66%). Factors associated with pre-frailty were: low education (PR=1.37; 95% CI: 1.11-1.71), dependence on basic (PR=1.39; 95% CI: 1.22-1.59) and instrumental activities of daily living (PR=1.58; 95% CI: 1.40-1.78), depressed mood (PR=1.58; 95% CI: 1.40- 1.78). =1.53; 95% CI: 1.31 1.78), negative self-rated health (PR=1.39; 95% CI: 1.15-1.69), polypharmacy (PR=1.30; CI 95%: 1.13-1.50), and nutritional risk (PR=1.27; 95% CI: 1.09-1.46). Conclusion: pre-frailty prevalence was higher than that found in other studies that used the same instrument, and the variables associated with this outcome demonstrated the existence of a common phenomenon among older adults. These are important results, as they highlight the need for investment in research and preventive interventions on the clinical, functional and social conditions of this population. Furthermore, it is necessary to invest in professional training programs for the comprehensive care of older adults, especially with regard to frailty assessment and prevention.